Observational evidence for constant gas accretion rate since z = 5. (29th June 2017) - Spring, Eleanor F.; Michałowski, Michał J.
Abstract: Star formation rate density (SFRD) has not been constant throughout the history of the Universe. The rate at which stars form greatly affects the evolution of the Universe, but the factors which drive SFRD evolution remain uncertain. There must be sufficient amount of gas to fuel the star formation, either as a reservoir within a galaxy, or as inflow from the intergalactic medium (IGM). This work explores how the gas accretion rate on to galaxies over time has affected star formation rate. We propose a novel method of measuring cosmic gas accretion rate. This involves comparing the comoving densities of available H i and H2 gas and the densities of existing stars at different redshifts. We constrained gas accretion until z = 5, and we found that the gas accretion rate density (GARD) is relatively constant in the range from z = 5 to z = 0. This constancy in the GARD is not reflected by the SFRD, which declines significantly between z = 1.0 and z = 0. This work suggests that the decline is not due to a reduction in GARD.